Study on the anisotropic permeability in different rank coals under influences of supercritical CO2 adsorption and effective stress and its enlightenment for CO2 enhance coalbed methane recovery. (15th February 2020) - Niu, Qinghe; Cao, Liwen; Sang, Shuxun; Zhou, Xiaozhi; Wang, Wei; Yuan, Wei; Ji, Zhongmin; Wang, Haichao; Nie, Yan
Abstract: The permeability of coal reservoir is dynamically changed during CO2 enhance coalbed methane recovery projects (CO2 -ECBM) and is controlled by the two main influencing factors: effective stress and CO2 adsorption. Six coal core samples parallel and vertical bedding plane directions were drilled, which were then adopted to conduct the permeability tests under conditions of cyclic loading/unloading and supercritical CO2 saturation. Results show that the permeability is depended on the coal rank, the middle rank coal possesses the highest initial permeability because of its moderate compaction and largely generated cleats during the coalification. The permeability is anisotropic, manifesting in the permeability in parallel bedding plane direction is larger than that in the vertical bedding plane direction. The stress sensitivity coefficient and IPLRi in parallel bedding plane direction exceed that in vertical bedding plane direction, however, PALR exhibits the opposite law. Hereat, the fractures parallel to bedding plane are susceptible to the stress change and the cleats vertical to bedding plane are sensitive to the ScCO2 adsorption. In view of the irreversible permeability damage by the stress change and CO2 adsorption, experiments in this paper confirms that prefracturing can dramatically decrease the IPLRi, stress sensitivity coefficient and PALR of coal seams, which may be the potential and effective measure to enhence the injectivity of CO2 in coal seams.